Pendekatan Guru Bimbingan Konseling dalam Membangun Kesadaran Disiplin Siswa di SMP Pecawan Medan - Naila Dwi Fani; Tri Nike Wulandari Lubis; Gladis Pradana; Nanda Fitria Ningsih; Christin Debora; Aman Simaremare; Doni Irawan Saragih (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
In the school environment, efforts to build students' discipline awareness are a challenge in themselves, especially amidst social dynamics and technological developments that influence adolescent behavior. The purpose of this study is to examine discipline issues and describe the approaches applied by BK teachers at SMP Pecawan Medan in building students' discipline awareness. With a qualitative descriptive research method, case study design. The results of the study indicate that student discipline problems at SMP Pecawan Medan are quite complex, covering various violations such as lateness, violations of rules, to deviant behavior. BK teachers apply a humanistic and educational approach through personal dialogue, individual counseling, a combined preventive and curative approach, and behavioral evaluation. The approach taken by BK teachers does not only emphasize punishment, but also on understanding the reasons for violations and character building. Parental involvement and collaboration between schools also strengthen the effectiveness of coaching.